A developmental view of mentoring talented students in academic and nonacademic domains. Issue 1 (6th December 2019) - Subotnik, Rena F.; Olszewski‐Kubilius, Paula; Khalid, Maha; Finster, Heather
Abstract: The role of mentors for talented students varies according to developmental level and domain. Domains differ as to when they begin, peak, and end. Therefore, mentoring at the beginning of a talent trajectory may take place in middle school for a science student and in elementary school for a violinist. In the later stages of talent development, mentors are more likely to select their protégés than to be organizationally matched with mentees. As mentees gain the requisite skills and knowledge, mentors place more emphasis on modeling and coaching for psychosocial skills and insider knowledge (access to networks of information, attitudes, and behaviors rewarded by gatekeepers) that allow their mentees to stand out and, if necessary, endure pushback derived from proposing creative ideas or performances that challenge the status quo. The conclusions reported here are derived from studies of mentoring talented students, with an emphasis on identifying similarities across domains, and recognition that mentors' provision of insider knowledge is particularly important for low‐income children and youth. Abstract : This paper offers a conceptualization of mentoring for talented children, youth, and young adults as they transition from novices to experts. The conclusions reported here are derived from studies of mentoring talented students, with an emphasis on identifying similarities across domains. The authors argue for the role of psychosocial skill training and provision of insider knowledge as increasingly important contributions made by mentors to their mentees.